What do customers expect from social housing providers in the UK?. (2017) - Sagoo, Amrit; Khalfan, Malik M.A.
This research presents a preliminary investigation to understand the customers' perception and expectations of service delivery in relation to social housing within the UK. The aim of this paper is firstly to present an overview of the customer and the main providers of social housing. Secondly, the paper explores the nature of service delivery in social housing and its importance in achieving customer satisfaction. Thirdly, this paper reports on the survey undertaken with 60 tenants (customers) residing with six registered social landlords (RSLs) during focus group workshops. The findings from the survey suggest that there are numerous factors that affect customer expectations including quality of accommodation, fair rent, value for money, services, and quality of repairs undertaken either as part of day to day repairs or in the form of planned maintenance.